2010
DOI: 10.1074/jbc.m109.035865
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Activity Is Required for the in Vivo Functions of CARM1

Abstract: CARM1 is one of nine protein arginine methyltransferases that methylate arginine residues in proteins. CARM1 is recruited by many different transcription factors as a positive regulator. Gene targeting of CARM1 in mice has been performed, and knock-out mice, which are smaller than their wild-type littermates, die just after birth. It has been proposed that CARM1 has functions that are independent of its enzymatic activity. Indeed, CARM1 is found to interact with a number of proteins and may have a scaffolding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 37 publications
8
65
0
Order By: Relevance
“…The methyltransferase activity of CARM1 is required for its ability to regulate transcription of pS2 (TFF1), a standard ERα target gene (5). Moreover, the enzyme-dead CARM1 knockin mice have defects similar to those seen in their knockout counterparts (6). These observations suggest that the enzymatic activity of CARM1 is indispensable for the majority of CARM1's in vivo functions.…”
mentioning
confidence: 55%
“…The methyltransferase activity of CARM1 is required for its ability to regulate transcription of pS2 (TFF1), a standard ERα target gene (5). Moreover, the enzyme-dead CARM1 knockin mice have defects similar to those seen in their knockout counterparts (6). These observations suggest that the enzymatic activity of CARM1 is indispensable for the majority of CARM1's in vivo functions.…”
mentioning
confidence: 55%
“…Although the basal levels of p21 and Gadd45 mRNA varied in the three MEF cell lines, it is inappropriate to compare basal levels between these cell lines, since each cell line was derived from a different mouse. CARM1 +/+ and CARM1(KI) MEF cells express similar levels of CARM1 protein (Kim et al 2010). It is interesting to note that DNA damage-induced expression of both p21 and Gadd45 requires BRCA1 (MacLachlan et al 2002;Aylon and Oren 2007).…”
Section: Synergistic Enhancement Of the Brca1 Brct Domain Transcriptimentioning
confidence: 99%
“…), MEF(CARM1 KI) (with a R169A mutation that eliminates methyltransferase activity), MEF(CARM1 rescued; i.e., with the knockout reversed by Flipase) (Yadav et al 2003;Cheng et al 2007;Kim et al 2010), and 293T cells were maintained in DMEM supplemented with 10% fetal bovine serum. Transfections were performed with F1 Targefect reagent (Targeting Systems) for 293T cells and with Lipofectamine 2000 (Invitrogen) for MEF cells, according to the manufacturers' protocols as described previously .…”
Section: Mef Wild-type Mef(carm1mentioning
confidence: 99%
“…Mice with a targeted deletion of Carm1 (Carm1 / ) are small and have defects in the differentiation of multiple cell types including T cells and adipocytes (Kim et al, 2004;Yadav et al, 2008;Yadav et al, 2003). Recently, it has been shown that mice carrying the enzyme-dead form of CARM1 phenocopy the Carm1 knockout, suggesting that CARM1 requires enzymatic activity for its known cellular functions (Kim et al, 2009). Carm1 knockout animals die shortly after birth and suffer from respiratory distress.…”
Section: Introductionmentioning
confidence: 99%